Performance of Neonatal Unit, Arifin Achmad Hospital, Pekanbaru - Dewi Anggraini Wisnumurti (Paediatrica Indonesiana, 2012)
Background Arifin Achmad Hospital is the largest hospital inRiau Province, Indonesia, which serves as referral hospital andoffers tertiary care for sick neonates.Objective To review the performance of the Neonatal Unit ofArifin Ahmad Hospital as a mean to further improve the overallcare Mth specific interest to improve neonatal outcomes.Methods We collected the clinical data of all patients admitted tothe Neonatal Unit from 2008 to 2010. Diagnoses were classifiedaccording to the International Statistical Classification of Diseasesand Related Health Problems 10th Revision (Revised leD 10). Weevaluated the overall performance of the unit, including numberof beds, number of patients, and bed occupancy rates (BOR). Thespectrum of diagnoses was also described. Associations betweenclinical characteristics and patient outcomes were analyzed usingunivariate Chi square test.Results The number of available beds increased from 10 beds in2008 to 24 beds in 2010, thereby decreasing the BORfrom 112%in 2008 to 82% in 2010, despite the yearly increase in numberof patients (702 in 2008, 772 in 2009, and 821 in 2010). MostNeonatal Unit patients were male, aged 0ô€’3 days at the time ofadmission, had birth weights of 2500ô€’4000 grams, born in RSUDArifin Achmad and were born vaginally. Respiratory problems,prematurity and infections were the three main reasons foradmission. Birth weight, the presence of congenital malformations,referral status, and < 7 day length of stay were associated withmortality.Conclusions The performance of the unit increased during the3ô€’year period of study. Most patients admitted had respiratoryproblems, fetal growth problems, or infections. We found that birthweight, congenital malformations, referral status, and decreasedlength of stay were prognostic factors for patient outcomes.[Paediatr rndones. 2012;52:356-61].